2022
DOI: 10.26434/chemrxiv-2022-ss450
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modelling mercury sorption of a polysulfide coating made from sulfur and limonene

Abstract: A polymer made from sulfur and limonene was used to coat silica gel and then evaluated as a mercury sorbent. A kinetic model of mercury uptake was established for a range of pH values and concentrations of sodium chloride. Mercury uptake was generally rapid from pH = 3 to pH = 11. At neutral pH, the sorbent (500 mg with a 10:1 ratio of silica to polymer) could remove 90% of mercury within one minute from a 100 mL solution 5 ppm in HgCl2 and 99% over 5 minutes. It was found that sodium chloride, at concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…20 This low chain mobility in poly(S-r-squalene) proved to be less effective in improving Li-S cell capacity retention (Table 1, $67% initial capacity at 20th discharge, cycled at C/10 or 167.5 mA g À1 ) 20 compared to poly(Sr-DIB) (Table 1, $74% initial capacity at 20th discharge, cycled at C/10 or 167.5 mA g À1 ). 14,21 Despite this result for poly(S-rsqualene), the polymer from 1,5-diene limonene, poly(S-rlimonene), initially developed by Crockett et al, 15,32 exhibits high capacity retention values (Table 1, 97% of initial capacity at 300th discharge, cycled at 0.5C, 1C undened) 33 surpassing that of poly(S-r-DIB). Such promising results using poly(S-r-limonene) prompts further investigation on inverse vulcanized copolymers using 1,5-diene crosslinkers and how they can be effectively used or tuned to show optimal performance as electrode materials for Li-S cells.…”
Section: Introductionmentioning
confidence: 94%
“…20 This low chain mobility in poly(S-r-squalene) proved to be less effective in improving Li-S cell capacity retention (Table 1, $67% initial capacity at 20th discharge, cycled at C/10 or 167.5 mA g À1 ) 20 compared to poly(Sr-DIB) (Table 1, $74% initial capacity at 20th discharge, cycled at C/10 or 167.5 mA g À1 ). 14,21 Despite this result for poly(S-rsqualene), the polymer from 1,5-diene limonene, poly(S-rlimonene), initially developed by Crockett et al, 15,32 exhibits high capacity retention values (Table 1, 97% of initial capacity at 300th discharge, cycled at 0.5C, 1C undened) 33 surpassing that of poly(S-r-DIB). Such promising results using poly(S-r-limonene) prompts further investigation on inverse vulcanized copolymers using 1,5-diene crosslinkers and how they can be effectively used or tuned to show optimal performance as electrode materials for Li-S cells.…”
Section: Introductionmentioning
confidence: 94%
“…However, while chemisorption increases selectivity, it also makes regenerating the sorbent more challenging. Breaking the bonds between the sorbent and the metal can be difficult to accomplish while maintaining the chemical and physical integrity of the sorbent . Conversely, gas adsorption onto polysulfides is driven by physisorption, resulting in a sorbent that is less selective, but efficient to regenerate .…”
Section: Inverse Vulcanized Polysulfidesmentioning
confidence: 99%
“…To avoid the production of H 2 S, one possibility is the use of highly acidic or basic conditions to degrade the polysulfide. Acid stability studies of poly­(S- r -limonene) revealed that, at pH >11, the polysulfide degraded and mercury was leached back into the water . However, the degradation products of such a system have not been studied.…”
Section: End Of Lifementioning
confidence: 99%
“…17 Depending on the intended use, the choice of crosslinker and the quantity of sulfur can be used to modify or tune the morphology and properties of the crosslinked sulfur polymer. A wide range of sulfur polymers based on different crosslinkers, such as limonene, 18,19 styrene, fatty acid derivatives like vegetable oil, canola oil, etc., 20 are reported and explored for other fields such as optics fertilizers and as components in solar cells, etc. 14,[21][22][23][24][25][26][27][28][29] Moreover, sulfur is a soft Lewis base; considering (Hard-Soft-Acid-Base) HSAB theory, the sulfur polymer can be exploited to form covalent bonds with soft Lewis acids; hence it has been receiving significant attention in recent years with heavy metal sorption.…”
Section: Introductionmentioning
confidence: 99%